Dealing with cost and time in the Portuguese construction industry - Moura, Helder M. Pinto (2007)
Most construction projects in Portugal do not fully achieve the main management functions, namely cost and time. Accordingly, the competitiveness of the Portuguese construction industry has been ranked fairly low. A survey was conducted among the main construction stakeholders to help clarify the reasons for this problem. The inquiry used for the survey focused on the characteristics of major projects concluded in the last years and on specific data on the attainment of cost and schedule objectives. Research revealed that clients and contractors agree that major causes for cost overruns were due to design errors, direct changes ordered by the client and different site conditions due to geological and geotechnical obstacles. Client liability, design problems and the project specifics were the main causes indicated by clients and contractors for project delays. However, clients also specified main responsibilities for project delays to inadequate construction management.